An Analysis of Code Switching in WhatsApp Group Communication - Mukhfizal Mukhfizal (Research in English and Education Journal, 2021)
This study aimed at investigating the types of code switching made by WhatsApp group members of “English Club”. It also tried to find out the members’ reasons made code switching from Indonesia to English or visa-versa. The result of study showed that there were three types of code switching used by member of “English Club” namely intra-sentential switching, inter-sentential switching, and tag switching. Intra-sentential switching was the most frequent types of code switching made by members during the chat. Meanwhile, for the reasons of code switching, the result showed that there were four reasons of code switching. Necessity to talk in a particular topic, repetition for clarification, show group identity and lack of vocabulary. In conclusion the use of code switching is a commonly phenomenon carried out by WhatsApp group members of “English Club” while chatting.